2018
DOI: 10.4149/neo_2018_170608n411
|View full text |Cite
|
Sign up to set email alerts
|

miR-483 is down-regulated in gastric cancer and suppresses cell proliferation, invasion and protein O-GlcNAcylation by targeting OGT

Abstract: MicroRNAs (miRNAs) are involved in the gastric carcinogenesis and progression. Here, we confirmed that miR-483 was frequently decreased in gastric cancer patients. The expression levels of miR-483 were negatively correlated with tumor stage, node metastasis and stromal invasion. Log-rank tests demonstrated that low expression of miR-483 was strongly correlated with poor overall survival in patients with gastric cancer. Moreover, ectopic expression of miR-483 remarkably suppressed gastric cancer cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…miRNAs, including miR-7, miR-302c, miR-483, miR-371a-3p and miR-218, have been indicated to be involved in the GC progression. 19,26,[28][29][30] Our previous study demonstrated that miR-146a/b could markedly inhibit invasion and metastasis of GC cells. 15 MiR-146a/b down-regulating UHRF1 (ubiquitin-like, containing PHD and RING finger domains 1) resulted in the activation of several tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…miRNAs, including miR-7, miR-302c, miR-483, miR-371a-3p and miR-218, have been indicated to be involved in the GC progression. 19,26,[28][29][30] Our previous study demonstrated that miR-146a/b could markedly inhibit invasion and metastasis of GC cells. 15 MiR-146a/b down-regulating UHRF1 (ubiquitin-like, containing PHD and RING finger domains 1) resulted in the activation of several tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 98%
“…4 E2F3 is frequently overexpressed in quite a few cancers and its decrease may block tumor progression. 7,26 E2F3 has been found to be implicated in thyroid cancer metastasis to lung and liver, but the specific mechanism remained undetermined. 8 The results from this study indicated that E2F3 was overexpressed in GC samples, and high level of E2F3 expression might tend to poor prognosis in GC folks.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In fact, it has been reported that a variety of miRNAs can function as biomarkers for the diagnosis and prognosis of human gliomas. 21 In recent years, miR-483 has been demonstrated to be downregulated in colon cancer, hepatocellular carcinoma and gastric cancer, 9,12,22 while it was upregulated in anaplastic thyroid cancer and Wilms' Tumor, 23,24 suggesting that the expression of miR-483 is distinct in different types of cancers. In this study, we found that miR-483 was low expressed in glioma tissues compared to the paracancerous normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, miR-483 inhibited cell proliferation, invasion in gastric cancer via OGT. 12 However, the roles of miR-483 in the recurrence and metastasis of glioma remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cell lines expressing wildtype p53, the high level of OGT/O-GlcNAcylation can stabilize the tumor suppressor p53, and stabilized p53 further promotes the acquisition of new pro-oncogenic activities including cell proliferation and metabolic changes, whereas the stabilization of p53 was not detected in cell lines with mutated p53 (36,37), indicating a role of O-GlcNAcylation in regulating ovarian cancer proliferation and progression. Moreover, data of aberrant OGT level in various cancer tissues is also collected and analyzed by UALCAN based on TCGA datasets ( Figure 1) (38)(39)(40). Taken together, the changes in OGT/O-GlcNAcylation level directly affect tumor occurrence and progression.…”
Section: Imbalanced O-glcnacylation In Cancer Cellsmentioning
confidence: 99%